EDUKASI PENGENDALIAN DAN PENCEGAHAN KOMPLIKASI PADA KASUS DM DI PUSKESMAS KARANG TALIWANG - Dewi Nur Sukma Purqoti; Dian Istiana; Zaenal Arifin; Baiq Ruli Fatmawati; Ilham Ilham (JURNAL PENGABDIAN MASYARAKAT AKADEMISI, 2024)
. Diabetes mellitus (DM) is one of the non-communicable diseases that are commonly found in society today, this disease has increased the number of cases very rapidly from year to year. Therefore, one intervention is needed to prevent and control DM, one of which is how to control blood sugar levels so that complications do not easily occur. Method: This community service method is carried out in the form of providing health education about controlling blood sugar levels and preventing complications in DM cases by means of lectures and distributing leflets after that followed by questions and answers and discussions. Results and Conclusions: from the results of the service, it can be concluded that Health Education with lecture methods and distributing leflets can increase public knowledge about controlling blood sugar levels and preventing DM complications, so that the community is expected to be able to implement blood sugar level control and prevention of complications in the DM case itself.